Strategi Promosi melalui Media Sosial dalam Meningkatkan Jumlah Siswa di SMP Fajrul Islam dalam Perspektif Islam - Sukarna, Sukarna (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to determine promotion strategies through social media in increasing the number of students at SMP Fajrul Islam, research methods. namely a descriptive qualitative method that emphasizes observing a phenomenon and researching more on the substance of the meaning of the phenomenon. The results of the study stated that in carrying out a promotion strategy to get students it could be done in two ways, namely 80% utilization of social media such as WhatsApp, Facebook. And Instagram. The 20% is done by going directly to the field promotions. The proper use of social media to promote schools is able to prove that schools can compete healthily to gain a good image in the eyes of society. The use of promotional social media can be done effectively and efficiently because it doesn't take up a lot of time so it can be done anytime and anywhere. continue to instill the most important religious teachings such as having a dhuha prayer program every morning, reading and writing the Koran, tahfidz qur'an, safinah books and muhadhoroh as a way to continue to instill Islamic Sharia in schools.